Fenvalerate exposure induces AKT/AMPK-dependent alterations in glucose metabolism in hepatoma cells - Sun, Lu; Cui, Zheng-Guo; Feng, Qianwen; Muhammad, Jibran Sualeh; Jin, Yu-Jie; Zhao, Songji; Zhou, Lingqi; Wu, Cheng-AI (Frontiers in Pharmacology, 2025)
BackgroundFenvalerate (Fen) is a synthetic pyrethroid insecticide significantly associated with an increased risk of type 2 diabetes. Tumor cells exhibit a shift in glucose metabolism, known as the Warburg effect. Accordingly, we aimed to elucidate whether Fen interferes with insulin signaling and affects hepatoma cell metabolism.MethodsThe cells were subjected to Fen to assess glucose uptake, acidification, oxygen consumption, and ATP production. ROS generation, mitochondrial membrane potentials, and protein expression were evaluated by flow cytometry, immunofluorescence microscopy, and western blot analyses.ResultsOur results demonstrated that Fen promotes glucose uptake, lactate production, and ATP generation in various cancer cells. Moreover, Fen enhanced insulin receptor phosphorylation and upregulated p-AKT/p-AMPK expression. Fen enhanced insulin receptor sensitivity and endocytosis via reactive oxygen species generation rather than the PP2B pathway. Additionally, the antioxidants N-acetyl-L-cysteine and ascorbic acid reversed the Fen-induced increase in glycolysis. Finally, chronic Fen exposure protected hepatoma cells against metformin-induced cell death via the AKT/AMPK pathway.ConclusionThese findings raise concerns regarding the safety of Fen and its potential role in altering cancer cell metabolism, affecting insulin signaling and treating drug resistance, thereby necessitating further research.